Rumpel-Leede Phenomenon in a Patient with Laboratory Markers Positive for Sjögren Disease. Issue 11 (1st June 2016) - Ramme, Austin J.; Gales, Jordan; Stevens, Nicole; Verma, Vijay; Egol, Kenneth
Abstract : Rumpel-Leede phenomenon is a rare clinical sign involving the appearance of purpura after application of a tourniquet or in noninvasive arterial blood pressure monitoring. This sign has been most commonly associated with hypertensive and diabetic microvascular fragility and thrombocytopenia. We describe a case of Rumpel-Leede phenomenon in an otherwise healthy patient with positive laboratory markers for Sjögren disease, a previously undescribed relationship. We aim to inform physicians of this potential complication in patients with Sjögren disease and suggest special consideration be given to patients with autoimmune diseases with secondary vascular or dermal manifestations.